2021
DOI: 10.1070/qel17548
|View full text |Cite
|
Sign up to set email alerts
|

Emission of xenon in the spectral range of 120 – 800 nm upon excitation by diffuse and spark discharges

Abstract: Xenon emission in the spectral range of 120 – 800 nm upon excitation by subnanosecond voltage pulses is investigated. Excitation is performed using diffuse and spark discharges in an inhomogeneous electric field at a xenon pressure ranging from 0.3 to 3 atm. It is shown that xenon excitation by a series of successive 0.7-ns voltage pulses with a pause of 30 ns leads to a decrease in the second-continuum radiation intensity by the second and subsequent voltage pulses and an increase in the first-pulse afterglow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus, short high-voltage pulses were applied to the gaps, providing a sharply inhomogeneous electric field near electrodes. With a high degree of probability, it can be concluded that in the above references, runaway electrons could appear and, similarly to [9][10][11][12][13][14], provide preionization and diffuse discharge formation.…”
Section: Hydrogen Lasermentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, short high-voltage pulses were applied to the gaps, providing a sharply inhomogeneous electric field near electrodes. With a high degree of probability, it can be concluded that in the above references, runaway electrons could appear and, similarly to [9][10][11][12][13][14], provide preionization and diffuse discharge formation.…”
Section: Hydrogen Lasermentioning
confidence: 94%
“…The VUV emission intensity in mixtures with Ar decreased due to the development of diffuse plasma inhomogeneities. The discharge contraction led to the appearance of continuum radiation in the visible region, associated with the recombination radiation of the spark leaders and channels [10].…”
Section: Hydrogen Lasermentioning
confidence: 99%
See 2 more Smart Citations